Essential jobs, remote work and digital surveillance: Addressing the COVID-19 pandemic panopticon - Aloisi, Antonio; De Stefano, Valerio (Wiley, 2021)
An unprecedented COVID-19-induced explosion in digital surveillance has reconfigured power relationships in professional settings. This article critically concentrates on the interplay between technology-enabled intrusive monitoring and the augmentation of managerial prerogatives in physical and digital workplaces. It identifies excessive supervision as the common denominator of “essential” and “remotable” activities, besides discussing the various drawbacks faced by the two categories of workers during (and after) the pandemic. It also assesses the adequacy of the current European Union legal framework in addressing the expansion of data-driven management. Social dialogue, workers' empowerment and digital literacy are identified as effective ways to promote organizational flexibility, well-being and competitiveness.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura; ODS 12 - Producción y consumo responsables; ODS 11 - Ciudades y comunidades sostenibles